2018
DOI: 10.1111/eip.12709
|View full text |Cite
|
Sign up to set email alerts
|

Early interventions in a US military FIRST episode psychosis program

Abstract: These data support our view that the structure of the military and military healthcare system markedly shortens the DUP for military service members who experience first episode psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…40,41 The significance of early intervention and development of prevention strategies for vulnerable populations are increasingly gaining ground in the military environment. 42 A recent study in the Greek army revealed that the duration of untreated psychosis is minimal for soldiers experiencing a first episode psychosis compared to the average time in the community. 21 This may be of particular importance for the later progression and course of the psychotic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 The significance of early intervention and development of prevention strategies for vulnerable populations are increasingly gaining ground in the military environment. 42 A recent study in the Greek army revealed that the duration of untreated psychosis is minimal for soldiers experiencing a first episode psychosis compared to the average time in the community. 21 This may be of particular importance for the later progression and course of the psychotic disorder.…”
Section: Discussionmentioning
confidence: 99%